Four new species of the spider genus Telema (Araneae, Telemidae) from Southeast Asia - Wang, Chunxia; Li, Shuqiang (Zootaxa, 2010)
Four new species of the spider genus Telema from Southeast Asia are described and illustrated: T. acicularis sp. nov. and T. anguina sp. nov. from Thailand, T. fabata sp. nov. from Singapore, and T. malaysiaensis sp. nov. from Malaysia.